Implementation Model of Regional Spatial Planning Policy in Realizing Sustainable City Development in Banjar City: (Banjar City Regional Regulation Study No. 9 of 2014 concerning Banjar City Spatial Planning) - David Abdillah Al Amin; Kamal Alamsyah; Ummu Salamah (Doctoral Program of Social Science Pasundan University, 2022)
The main problems in this study are directed at the model of the implementation of the Regional Spatial Planning policy in practice has not run effectively in realizing sustainable urban development in Banjar City. The research method used by researchers is descriptive analysis, while the type of approach used in this study is qualitative. Descriptive analysis method aims to describe complex social reality by applying concepts that have been developed in social science / public administration. Whereas the qualitative approach was chosen with the consideration that this approach is expected to obtain true data and be able to examine research problems in depth so that the expected results can be obtained. The results of the study can be stated that there are factors that lead to the implementation of the Regional Spatial Plan (RTRW) policy in realizing sustainable city development in Banjar City can run effectively, namely Policy standards and objectives, Resources and incentives, The quality of inter-organizational relationship , The characteristics of implementation agencies, the economic, social and political environment and the 'dispositon' or response of the implementers. However, based on the results of the research, these factors have not been entirely effective. The factors that have not been implemented effectively are the Policy standards and objectives and the